Apical root resorption after orthodontic treatment a comparison of severity between adults and adolescents - Carreon, Charlotte Ann Z.
This study aimed to ascertain if the degree of Apical Root Resorption occurs in greater severity with adults than in adolescents. A total of 85 debonded cases of patients from the UPCD Postgraduate School of Orthodontics were looked into but the subjects were narrowed down to 33 since they had to quality for a specific age range. The subjects were classified into 2 groups, the Adult Group which is comprised of patients aged 21-33 years and Adolescent Group composed of patients with ages ranging from 11-16 years. The pre- and post-treatment panoramic radiographics were examined and the tooth lenght of the maxillary incisors were then measured using a vernier caliper. However, to account for the consequential project error of enlargement in panoramic films, the measurements were divided by 1.03. The discrepancy between the pre- and post-treatment measurements were tabulated. The mean, standard deviation and the percentages of actual root loss was computed. For the Adult Group, the mean of the discrepancies of pre- and post-treatment measurements for 11 is 1.59 with a standard deviation of 1.15 while tooth #21 has a mean of 2.17 with a standard deviation of 1.15. The adolescent group, on the other hand, has a mean of 1.56 for tooth #11 with a standard of 0.91. Tooth #21 on the other hand, has a mean of 1.82 with a standard deviation of 1.23 A paired t-test at 0.5 level of confidence was done to determine the statistical significance of the data. The results showed that there is a slight, almost negligible difference between the amount of resorption in 11 observed in adults compared with the younger population. Tooth number 21 and a bigger and more significant difference. We can therefore conclude that there is a slight difference between the amount of resorption observed in adults compared with adolescents.